2016
DOI: 10.1021/acs.jpcc.6b03709
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Model Behavior in an Ethylene Carbonate Electrolyte Using Molecular Dynamics

Abstract: The performance of lithium-ion batteries is strongly dependent on the nature of the electrolyte, and a better understanding of the role of the electrolyte in ion transport and the formation of the solid–electrolyte interface is critical for the performance improvement of such batteries. New cathode and anode materials demand new and/or improved electrolytes that are less sensitive to operating conditions and provide higher conductivity and mobility of ions between electrodes. A clear understanding of the solva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 58 publications
(107 reference statements)
5
81
0
Order By: Relevance
“…56 in which, this combination of force elds was used successfully in a Li-ion full nanobattery with Si electrodes, 56 and also with a very similar combined force-eld by Kumar et al 59 in the modelling of Li-diffusion through the electrolyte, obtaining good agreement with experimental results.…”
mentioning
confidence: 80%
“…56 in which, this combination of force elds was used successfully in a Li-ion full nanobattery with Si electrodes, 56 and also with a very similar combined force-eld by Kumar et al 59 in the modelling of Li-diffusion through the electrolyte, obtaining good agreement with experimental results.…”
mentioning
confidence: 80%
“…For example, quantum calculations track electrons and can characterize decomposition of electrolytes at anode surfaces [ 8 , 9 , 22 , 27 , 28 ]. These methods include ab initio molecular dynamics (AIMD), which have the drawback of computational expense and the concomitant limitation to small systems and time scales [ 29 31 ]. On the other hand, if chemical changes such as chemical bond rearrangement are essential to the study, AIMD provides natural perspectives on those phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…32) and that the distance between Li+ and oxygen of EC or DMC is z0.2 nm. 33 The lithiation-delithiation of LTO is a complex process, which was believed to be kinetically dominated by electronic conductivity. 27 However, it was recently reported that the electronic conductivity is only one of the crucial factors, especially in the case of nanostructured LTO, where Li ion transport ability becomes a predominant or competitive factor along with electronic conductivity.…”
Section: Resultsmentioning
confidence: 99%